(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Carrot Farming Development Strategy during the Covid-19 Pandemic in Pancasari Village, Sukasada District, Buleleng Regency. Horticultural crops are plants with high selling value that can bring benefits to the lives of the community and small to large scale farmers. One of the potential horticultural commodities in Pancasari Village, Bali Province is carrots. Carrot (Daucus carota L) is a strategic crop and can open up new jobs because the cultivation to post-harvest process requires a lot of labor which will have a positive impact on increasing the economic welfare of the community. However, when the Covid-19 Pandemic hit, farmers experienced problems in managing carrot plants, where the supply of carrot plants to consumers temporarily stopped. The purpose of this study is to analyze general, alternative and priorities strategies for the development of carrot farming which was constrained during the Covid-19 Pandemic using descriptive analysis to identify internal-external factors, SWOT Analysis which followed by analyzing the priority strategies using QSPM Analysis. Based on the results of the IFAS and EFAS matrices, two factors with the highest scores were obtained, namely the availability of large land, and the availability of financial institutions. The results of this study obtained the priority strategy with the highest score is the need for government support in minimizing decreased productivity.